Can educational expansion improve income inequality in China? Evidences from the CHNS 1997 and 2006 data - Guangjie Ning (Institute for the Study of Labor (IZA), 2010)
Rapid education expansion and rising income inequality are two striking phenomena occurring in China during the transitional period. Using the China Health and Nutrition Survey (CHNS) data collected in 1997 and 2006, this paper studies how education affects individual earnings during the transitional process. We find that education accounts for only a small fraction of personal earnings and income gap between different groups. We analyze the underlying mechanism of the impact of education on earnings. More educated people tend to enter state-owned sectors, have a low probability of changing jobs in the labor market and work less time; all of these will have a pronounced impact on earning and income inequality. Quantile regression analysis shows that the low-income group's education return rate is lower, which helps little in narrowing income gap. We decompose the earning gap into four factors: population effect, price effect, labor choice effect and unobservable effect. In explaining the earning gap in China, the price effect is more important than the population effect. The labor choice effect is also significant. We conclude that increasing educational expenditure with no complementary measures such as reforming the education system and establishing a competitive labor market helps less in reducing income inequality.
Keywords: I20; J31; O15; 330; education expansion; income gap; rate of return to education; labor market; Bildungspolitik; Wirkungsanalyse; Lohnstruktur; Einkommensverteilung; Bildungsertrag; China